Rapid and simple determination of histamine-N-methyl transferase activity by high-performance liquid chromatography with UV detection - Hajime Inoue; Ken-Ichi Hisamatsu; Miki Yamauchi; Norio Kumagai (Mediators of Inflammation)
A rabid, simple and low-cost assay method of histamine-N-methyltransferase activity was developed. Methylhistamine, which was separated from the enzymatic reaction system on reversed-phase high-performance liquid chromatography using an ion-paired chromatographic technique, was detected spectrophotometrically at 226 nm. The mobile phase used for the separation of methylhistamine was 0.05 M NH4H2 PO4 (pH 3.0) containing 2 mM of sodium octanesulfonate. The new assay technique could detect methylhistamine as an enzyme activity product of histamine-N-methyltransferase in the brain and kidney of rats. Chloropheniramine maleate, an antihistamine, activated the histamine N- methyltransferase. Whether neurotransmitter or neuromodulator, the role of histamine in the brain has not yet been made clear. Therefore, the present method could be applicable for the enzymatic investigation of histamine metabolism in central nervous system or inflammatory reactions.